Penyuluhan Pendidikan Karakter Sebagai Pilar Dalam Membangun Moral Dan Akhlak Anak - Muhammad Tri Ramdhani; Supriadi Supriadi; Hunainah Hunainah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
At this time character education can no longer be ignored because of the role that is very important to improve the moral and morals of children because the moral children of today's nation are getting away from the good word with the modern era of changes that are cultivated in information technology that is growing rapidly renewal. In this PKM activity, to overcome the apparent problems, the team of lecturers Prodi PAI offers PKM implementation with the form of Character Education Education as a Pillar in Building Moral And Child Morals held at PKBM Luthfillah, which is opened for PKBM and general participants. Considering many people who do not have formal education or equality, this counseling is expected to be useful and equip the community about understanding the guidance of Islam in educating children at home in general and about the procedures for the implementation of personal Islamic character education that can be maximally endeavored by each family members, both the head of the family and the representatives and all their members, so as to assist the government in socializing character education for the grass root community in practice level.